COMMUNITY ENTREPRENEURSHIP SKILL THROUGH BANANA AND CHILI PRODUCT TO IMPROVE THE ECONOMY OF RURAL COMMUNITIES - Fayruzah El-Faradis (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Community entrepreneurship skill   is an effort and strategy in producing the product based on the owned–asset. Through this, ideas emerged for processing raw materials into processed goods that were worth selling, as well as Taddan village which was the target of this community empowerment activity. Taddan village with its own primary asset such bananas and chilies will increase the economic growth of the village through processing the bananas and chilies into economical and selling products. To achieve this goal, the author used the Asset-Based Community Development (ABCD) method. This method was developed from the owned assets, not from problems. With the ABCD method, the author tried to empower rural communities, especially Taddan village, in processing banana and chili products into worth selling products. The result of this activity is the launching of banana chips and sambal cumi kribo from processed bananas and chilies which are well received, and got many orders from the local community.